2018
DOI: 10.1002/jae.2619
|View full text |Cite
|
Sign up to set email alerts
|

Exact computation of GMM estimators for instrumental variable quantile regression models

Abstract: SummaryWe show that the generalized method of moments (GMM) estimation problem in instrumental variable quantile regression (IVQR) models can be equivalently formulated as a mixed-integer quadratic programming problem. This enables exact computation of the GMM estimators for the IVQR models. We illustrate the usefulness of our algorithm via Monte Carlo experiments and an application to demand for fish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The actual situation is that economic variables are often skewed because they are complex and volatile. Moreover, the extreme values (i.e., maximum and minimum) of economic variables often imply important information and have important impacts on the related socio‐economic phenomena (Chen & Lee, 2018). The quantile regression model does not require economic variables to follow a normal distribution and is resistant to outliers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The actual situation is that economic variables are often skewed because they are complex and volatile. Moreover, the extreme values (i.e., maximum and minimum) of economic variables often imply important information and have important impacts on the related socio‐economic phenomena (Chen & Lee, 2018). The quantile regression model does not require economic variables to follow a normal distribution and is resistant to outliers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kaplan and Sun (2017) and de Castro, Galvao, Kaplan, and Liu (2019) have suggested using smoothed estimating equations to overcome the non‐smoothness of the IVQR estimation problem; however, the nonconvexity persists. More recently, Chen and Lee (2018) have proposed to recast the IVQR problem as a mixed‐integer quadratic programming problem that can be solved using well‐established algorithms. However, efficiently solving such a problem is still challenging even for low‐dimensional settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, efficiently solving such a problem is still challenging even for low‐dimensional settings. Zhu (2018) has shown that if the normal∞ norm is used rather than the 2 norm, the problem admits a reformulation as a mixed‐integer linear programming problem, which can be solved more efficiently than the quadratic program in Chen and Lee (2018). This procedure typically requires an early termination of the algorithm to ensure computational tractability which is akin to a tuning parameter choice.…”
Section: Introductionmentioning
confidence: 99%
“…Kaplan and Sun (2017) and de Castro, Galvao, Kaplan, and Liu (2018) have suggested to use smoothed estimating equations to overcome the non-smoothness of the IVQR estimation problem, although the non-convexity remains. More recently, Chen and Lee (2018) have proposed to reformulate the IVQR problem as a mixed-integer quadratic programming problem which can be solved using well-established algorithms. However, efficiently solving such a problem is still challenging even for low-dimensional settings.…”
Section: Introductionmentioning
confidence: 99%